2005
DOI: 10.1038/nature03638
|View full text |Cite
|
Sign up to set email alerts
|

Lightning-induced intensification of the ionospheric sporadic E layer

Abstract: A connection between thunderstorms and the ionosphere has been hypothesized since the mid-1920s. Several mechanisms have been proposed to explain this connection, and evidence from modelling as well as various types of measurements demonstrate that lightning can interact with the lower ionosphere. It has been proposed, on the basis of a few observed events, that the ionospheric 'sporadic E' layer--transient, localized patches of relatively high electron density in the mid-ionosphere E layer, which significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
90
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 26 publications
14
90
1
Order By: Relevance
“…Thunderstorm‐originated perturbation in plasma distribution of the ionosphere is recently reported by many workers [ Vadas and Fritts , ; Davis and Johnson , ; Johnson and Davis , ; Davis and Lo , ; Immel et al ., ; Kumar et al ., , ; Lay et al ., , ]. Davis and Johnson [] reported correlation between the strength of sporadic E layer and lightning activity and suggested that these perturbations could be explained either by vertically upward propagating gravity waves generated from thunderstorm site or by vertical electric discharges or by a combination of these two mechanisms. Thunderstorm‐associated gravity waves longer than 5 min have been observed in the F region [ Lay et al ., ; Vadas and Liu , ] as well as in the D region [ Yue et al ., , ; Chou et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thunderstorm‐originated perturbation in plasma distribution of the ionosphere is recently reported by many workers [ Vadas and Fritts , ; Davis and Johnson , ; Johnson and Davis , ; Davis and Lo , ; Immel et al ., ; Kumar et al ., , ; Lay et al ., , ]. Davis and Johnson [] reported correlation between the strength of sporadic E layer and lightning activity and suggested that these perturbations could be explained either by vertically upward propagating gravity waves generated from thunderstorm site or by vertical electric discharges or by a combination of these two mechanisms. Thunderstorm‐associated gravity waves longer than 5 min have been observed in the F region [ Lay et al ., ; Vadas and Liu , ] as well as in the D region [ Yue et al ., , ; Chou et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Gravity waves are generated from overshooting cloud tops of thunderstorm [ Vadas and Fritts , ; Lay et al ., ], may propagate vertically upward, and transfer energy from the sight of lightning into the ionosphere. Thunderstorm‐originated perturbation in plasma distribution of the ionosphere is recently reported by many workers [ Vadas and Fritts , ; Davis and Johnson , ; Johnson and Davis , ; Davis and Lo , ; Immel et al ., ; Kumar et al ., , ; Lay et al ., , ]. Davis and Johnson [] reported correlation between the strength of sporadic E layer and lightning activity and suggested that these perturbations could be explained either by vertically upward propagating gravity waves generated from thunderstorm site or by vertical electric discharges or by a combination of these two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric studies have found evidence of D-layer heating due to thunderstorm quasi-electrostatic fields [Inan et al, 1996;Pasko et al, 1995], evidence of direct heating of the D-layer due to lightning electromagnetic pulses [Cheng and Cummer, 2005;Cheng et al, 2007], and evidence of atmospheric gravity wave (AGW) influence on the E-region ionosphere (100-150 km) [Davis and Johnson, 2005;Johnson and Davis, 2006]. Stratospheric AGW studies have shown neutral density fluctuations at altitudes of 60-90 km due to tropospheric thunderstorms activities [Taylor and Hapgood, 1988;Dewan et al, 1998;Sentman et al, 2003;Yue et al, 2009], and the electron density at this altitude is expected to fluctuate in a similar manner.…”
Section: Introductionmentioning
confidence: 99%
“…Davis and Johnson [] found the statistical correlation between thunderstorm and localized enhancement of electron density in the E layer of the ionosphere, and concluded that the colocation of lightning and ionospheric enhancement can be explained by either vertically propagating gravity waves that transfer energy from the site of lightning into the ionosphere, or vertical electrical discharge, or by a combination of these two mechanisms. Woodman and Kudeki [] reported the observation by the Jicamarca Radio Observatory and showed the evidence that the increased electric field due to lightning can cause the plasma instability and plasma bubble in the F region of ionosphere.…”
Section: Resultsmentioning
confidence: 99%